Analysis Of Differences in Financial Distress Levels Between the Property & Real Estate Sub-Sector Industry and The Building Construction Sub-Sector Industry - Lestari, Lestari; Erdiana, Atty (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study investigates how the building construction industry in Indonesia Stock Exchange differs from the property and real estate industry in terms of financial bankruptcy rates. The population of this study is the property and real estate sub-sector and the building construction sub-sector in Indonesia Stock Exchange. The general objective of this study is to identify financial distress in the property & real estate and building construction industries and the level of financial distress of the property & real estate sub-sector and building construction sub-sector as a picture of the level of bankruptcy of the industrial group. While the specific objective is that companies can anticipate early and immediately make improvements in asset management and company financing. The results of this study can also be used as a reference for investors to restructure their investment portfolios with more accurate portfolio return estimation calculations. This study uses a purposive sampling method, with the consideration or criteria that the companies studied are companies that publish financial reports in 2022 and 2023 at least Q3. To measure the level of financial distress of the two industrial sub-sectors, the Springate (S-Score) analysis model is used with the Independent Sample T Test analysis technique. The results of this study indicate that there is no significant difference in financial distress in the property & real estate and building construction industries that go public on the Indonesia Stock Exchange.